New approach towards diagnostic coronarography at hospitals without their own angiography laboratories - Yu. G. Matchin; O. B. Privalova; D. V. Privalov; D. A. Zateyshchikov; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To assess safety, clinical and cost-effectiveness of a new method for invasive examination in coronary heart disease (CHD) patients: ambulatory coronary angiography (CAG) in hospitalised or ambulatory patients of a city clinical hospital (CCH) not having its own angiography laboratory.Material and methods. The study included 407 patients of the cardiology emergency department, Moscow CCH №51 (2001-2005), who underwent an ambulatory CAG at the angiography laboratory, Cardiology Research Institute, Russian Cardiology Scientific and Clinical Complex. Mean age of the participants was 56+10 years, with 281 (92 %) men, 236 (58 %) arterial hypertension (AH) patients, and 44 (11 %) diabetes mellitus (DM) patients. In total, 101 (25 %) and 17 (23 %) individuals were hospitalised to the CCH with myocardial infarction (MI) and unstable angina (UA) diagnosis, respectively.Results. CAG was successful in all 407 participants, including 311 with radial access, and 94 with femoral access. Mean total CAG duration, from anaesthesia start to bandaging puncture area, was 21,7±11 minutes; mean time of X-ray radiation - 4,2±2,4 minutes. On average, 135±29 ml of contrast and 2,6±0,7 catheters were used per patient. Mean time from procedure end to discharge was 3,9±1,2 hours. No major complications were observed, minor complication prevalence was 5 %. In cost-effectiveness analysis, ambulatory CAG reduced procedure costs by 19 %, comparing to the control group.Conclusion. Ambulatory CAG in CHD patients from a CCH without its own angiography laboratory, was safe, with low complication risk. Ambulatory CAG reduced mean procedure costs by 19 %, due to decreased hospitalisation expenses.